Developing an Integrated Web-Android Augmented Reality Learning Platform for Flat Sailing Science in Maritime Vocational Education - Endang Lestari; Masrupah; Wardimansyah Ridwan; Muhammad Hidayat L (Journal of Vocational, Informatics and Computer Education, 2026)
Purpose – This study aimed to develop and preliminarily validate an integrated web-Android-Augmented Reality (AR) learning media prototype for the Flat Sailing Science course in maritime vocational education. Methods –This study used Research and Development with the ADDIE model. Data were collected through needs analysis, observation, lecturer interviews, black-box functionality testing, and expert validation questionnaires using a five-point Likert scale. Material validation involved four senior lecturers, while preliminary media validation involved one multimedia expert. No cadet usability testing, user-acceptance testing, classroom implementation, or learning-outcome evaluation was conducted in this development cycle; therefore, the study is framed as prototype development, expert validation, and functional readiness testing only. Findings –The product generated three connected components: an AR-enhanced module, a web-based MARITIM IPD platform, and an Android application. Material validation produced an overall normalized descriptive score of 86.67%, while the one-expert media review produced a preliminary score of 85.71%. Black-box testing indicated that the main functions operated according to expected outputs in the final technical check. Research Implications –The product is suitable for expert-informed limited technical piloting, but the evidence remains preliminary. The current findings support descriptive content validity and functional readiness only; they do not demonstrate cadet usability, user acceptance, practicality, classroom implementation success, or learning effectiveness. Originality – This study presents a context-specific prototype that integrates AR visualization, web-based course management, and Android access for Flat Sailing Science in maritime vocational education. The originality claim is limited to this integrated maritime vocational configuration, not to AR learning media in general.